Carbon nanotube-linked hollow carbon nanospheres doped with iron and nitrogen as single-atom catalysts for the oxygen reduction reaction in acidic solutions. Issue 24 (6th June 2019) - Li, Jin-Cheng; Cheng, Min; Li, Tao; Ma, Lu; Ruan, Xiaofan; Liu, Dong; Cheng, Hui-Ming; Liu, Chang; Du, Dan; Wei, Zidong; Lin, Yuehe; Shao, Minhua
Abstract : A three-dimensional structure consisting of atomically dispersed Fe, N-doped hollow carbon nanospheres linked by carbon nanotubes was engineered as an electrocatalyst showing a high activity for oxygen reduction reaction. Abstract : Non-noble metal electrocatalysts toward the oxygen reduction reaction (ORR) are highly required to substitute expensive Pt/C as the cathode of proton exchange membrane fuel cells. However, the relatively low ORR activity of Pt-free catalysts under acidic conditions is the major issue. Herein, we engineered a three-dimensional structure consisting of atomically dispersed Fe, N-doped hollow carbon nanospheres linked by carbon nanotubes as an electrocatalyst for the ORR. Benefiting from the unique structure and high-density atomic Fe–N x sites, this new type of electrocatalyst showed an impressive ORR half-wave potential of 0.84 V and kinetic current density of 13.1 mA cm −2 at a potential of 0.8 V in acidic media, which was even better those of commercial Pt/C.